Prediction model of motorcycle accident in economic and driving behaviour factors - Putri, Friska; Arifin, Muhammad; Djakfar, Ludfi (Eastern-European Journal of Enterprise Technologies, 2022)
The number of motorized vehicles, especially motorcycles, is also offset by increased traffic accidents. As is known, road accidents essentially depend on four interrelated factors: human behavior, vehicle efficiency, environmental conditions, and the characteristics of the infrastructure. However, most accidents are attributable to the first three factors, almost always to improper user behavior. This study aims to determine motorcyclists’ socio-economic characteristics and conduct on the intensity of accidents. The research location is on the Pandaan-Purwosari National Road, Pasuruan Regency, Section 094‑098 (Surabaya-Malang). Three hundred forty respondents are motorcyclists who have experienced accidents in this segment. The research method is interviews and questionnaires—data analysis using Structure Equation Modeling (SEM), with software SmartPLS (Partial Least Square). The result of accident modeling Y=0.299X1+0.154X2+0.077X3+0.554X4. The first biggest influence on the chance of an accident is the characteristics of driving behavior (X4) exceeding speed (X4.10). The more often the rider exceeds the rate, the higher the chance of an accident. The second most significant influence of socio-economic characteristics (X1) is the age indicator (X1.2), the more mobility in the productive age, the higher the risk of accidents.